Perancangan Game untuk Menumbuhkan Kebanggaan terhadap Indonesia bagi Generasi Muda Indonesia - Faikar Izzani; Agung Eko Budiwaspada; Dudy Wiyancoko (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
Indonesia has the potential to become a respected developed nation, but until now it is still riddled with many problems. The pride of Indonesians to their country must be restored to motivate them to contribute to the nation. The media that will be used is mobile game with targeted segment Indonesian middle-class youth aged 15-21 years old. Research method used are observation, literature study, and interview with related parties. The content that will be used are native or acquired Indonesian technology and innovations. This is important because those are the base of a nation's development. Those contents are developed using captology and game designtheories. Basic brief of the designed game are 2D Visuals and using emergent gameplay. Interview with purposive sampling method to the target segment showed that they expect items consumed to be well designed and have significant values embedded. The game will be titled